(untitled) (Ustozlar uchun, 2025)
Idioms are a fundamental component of natural language, offering a vivid and concise means of expression that often defies literal interpretation. This article delves into the specific category of idioms used to describe human characteristics, personalities, and behaviors. It explores how these figurative expressions enrich communication by providing nuanced insights into individuals, often capturing complex traits in a memorable phrase. By examining a range of such idioms, categorized by the nature of the description (positive, negative, or neutral/situational), this paper highlights their semantic depth, cultural embeddedness, and the challenges they pose for non-native speakers. Ultimately, understanding and utilizing idioms describing people not only enhances linguistic proficiency but also fosters a deeper appreciation for the expressive power and cultural subtleties inherent in the English language.